Arthropods Diversity on Eggplant (Solanum melongena L.) Between Monoculture and Intercropping Farming System - Faljila, Fanisa; Rahardjo, Bambang Tri (University of Brawijaya, 2022)
This research aims to assess the diversity of arthropods, the abundance of Epilachna sparsa Auctt. and the feasibility of farming on monoculture and intercropping at the Agricultural Technology Assessment Center (BPTP). The research was conducted in BPTP of Riau Islands from January to April 2021. Sampling was carried out directly on fields with a total sample of 26 plants in the absolute method and 12 yellow sticky traps and 12 blue pan traps. The value of the diversity index (H') on the two fields belonged to the medium category. The richness index (R) on monoculture field was classified as being different from intercropping field which was classified as high. The evenness (e') on both fields was high and the dominance (C) showed that there was no arthropod that dominant. The t-test results for the intensity of E. sparsa's attack no significant effect on the two fields. The R/C ratio value on monoculture field was 1,32 and the R/C ratio value on intercropping had obtained a value of 1,85. The selling price on monoculture field was said to be a return on investment if it was sold at a price of Rp 5,285/kg while on the intercropping field was sold at Rp 6,351/kg.